Inhibition of thioacetamide induced liver intoxication and in-vitro antioxidant capacity of the Hugonia mystax - T, Rajananda Swamy; T, Mallikarjuna Rao; B, Ganga Rao (International Journal of Pharmacology and Toxicology, 2016)
Background: The using of synthetic drugs in adequate manner for the treatments of liver diseases are causes the different side effect. Therefore, there is need to search for new bioactive compounds to control liver diseases. In this point of view, we selected the medicinal plant H. mystax to evaluate of its antioxidant and hepatoprotective potentiality and isolation of its constituents, because it has been using in traditional medicine in the treatment of different diseases.Methods: Different extracts were prepared from H. mystax using maceration extraction process.Antioxidant activity was carried out using standard test procedures on Superoxide, Hydroxyl and DPPH free radicals. Hepatoprotective was tested using Thioacetamide (TAA) induced liver intoxication in rats.Results: The H. mystax extracts were showed dose dependent antioxidant and hepatoprotective activities. Tested extracts of H. mystax have more activity on hydroxyl free radical than superoxide and DPPH radicals and among all extracts hydroalcoholic extract showed more activity. The extracts of H. mystax significantly restored the altered biochemical parameters due to TAA induced liver intoxication and hydroalcoholic extract exhibited more significant activity. So, the hydroalcoholic extract was used for the isolation of phytochemical constituents through column chromatography and isolated HM-1 and HM-2 compounds and are identified as stigmasterol and Î²-sitosterol.Conclusion: From the results of the study, it could be conclude that H. mystax have the capacity in reduction of free radicals and normalization of liver function when it damage due to different liver intoxications and further research is need to evaluate more pharmacological activities and in isolation of most active bioactive compounds from H. mystax.